Pengaruh Commitment, Trust terhadap Customer Satisfaction dan Customer Loyalty - Bayu Aprilianto; Henny Welsa; Ida Bagus Nyoman Udayana (Widya Manajemen, 2022)
The purpose of this study was to determine the analysis of the influence of commitment, trust on customer satisfaction, and customer loyalty in Bento Kopi Yogyakarta. This research is quantitative research. The sample in this study is part of the target population, 100 respondents from Bento Kopi Yogyakarta customers, where the sample is determined by the Slovin formula. Data collection is done by using the method of collecting questionnaires or questionnaires. The data analysis technique used is a regression technique which is supported by the t-test and classical assumptions, the data that has been obtained is processed using SPSS 21. The results of this study indicate that the commitment variable has a positive effect on customer satisfaction based on the t-test with a value of 3,930 with a significance <0.05 so that Ho is rejected and Ha is accepted, the trust variable has a positive effect on customer satisfaction based on the t-test with a value of 8.163 with a significance <0.05 so that Ho is rejected and Ha is accepted, the customer satisfaction variable has a positive effect on customer loyalty based on the t-test with a value of 4.013 with a significance <0.05 so Ho is rejected and Ha is accepted, the commitment variable has a positive effect on customer loyalty based on the t-test with a value of 3.929 with a significance <0.05 so Ho is rejected and Ha is accepted, the trust variable has a positive effect on customer loyalty based on the test td with a value of 2.207 with a significance of <0.05 so that Ho is rejected and Ha is accepted.